Español (2023)
Clavulanic acid is a metabolite widely used with different combinations of antibiotics to counteract different infectious diseases. This metabolite is not produced in Colombia in spite of having a great demand at national level, apparently due to its high production costs and the little information available on the global process. In this research, different literature reports are used to present a generalized scheme of the production of this metabolite and, with the help of Aspen plus software, the implementation of a model to simulate the production process, including pretreatment, production and post-treatment or purification stages. The model is very useful to analyze costs or to evaluate eventual changes in the production process, constituting a useful tool for the study and understanding of the process, as well as for decision making regarding its eventual implementation.